Health promotion of women in the puerperal period: nurses’ knowledge and practices - Silva, Maria Adelane Monteiro da; Oliveira, Simone Helena dos Santos; Pinheiro, Ana Karina Bezerra; Ximenes, Lorena Barbosa; Barroso, Maria Grasiela Teixeira (Rev Rene, 2012)
This study aimed to verify the knowledge of the nurses from a philanthropic hospital in Ceará-Brazil concerning health promotion to investigate strategies adopted by the nurses in attention to the woman in the puerperal period with hospitalized children and its interaction with health promotion. A descriptive qualitative approach was developed at a philanthropic hospital of the municipal district of Sobral-CE, in the period of February to March of 2007. The interview was recorded and accomplished with six nurses and the analysis was based on the Technique of Elaboration and Analysis of the Meaning Units. Although the interviewees did not present a group of information that include satisfactorily the different focuses of the health promotion, the needs noticed by the same ones are combined with some inherent aspects to the fields of action of the health promotion. We considered that for the institutionalization of the health promotion is essential the transformation of values of the institution and their professionals so that they feel themselves as agents of change.